Effects of Coenzyme Q10 on the Biomarkers (Hydrogen, Methane, SCFA and TMA) and Composition of the Gut Microbiome in Rats - Anastasiia Yu. Ivanova; Ivan V. Shirokov; Stepan V. Toshchakov; Aleksandra D. Kozlova; Olga N. Obolenskaya; Sofia S. Mariasina; Vasily A. Ivlev; Ilya B. Gartseev; Oleg S. Medvedev (MDPI AG, 2023)
The predominant route of administration of drugs with coenzyme Q10 (CoQ10) is administration per os. The bioavailability of CoQ10 is about 2-3%. Prolonged use of CoQ10 to achieve pharmacological effects contributes to the creation of elevated concentrations of CoQ10 in the intestinal lumen. CoQ10 can have an effect on the gut microbiota and the levels of biomarkers it produces. CoQ10 at a dose of 30 mg/kg/day was administered per os to Wistar rats for 21 days. The levels of gut microbiota biomarkers (hydrogen, methane, short-chain fatty acids (SCFA), and trimethylamine (TMA)) and taxonomic composition were measured twice: before the administration of CoQ10 and at the end of the experiment. Hydrogen and methane levels were measured using the fasting lactulose breath test, fecal and blood SCFA and fecal TMA concentrations were determined by NMR, and 16S sequencing was used to analyze the taxonomic composition. Administration of CoQ10 for 21 days resulted in a 1.83-fold (p = 0.02) increase in hydrogen concentration in the total air sample (exhaled air + flatus), a 63% (p = 0.02) increase in the total concentration of SCFA (acetate, propionate, butyrate) in feces, a 126% increase in butyrate (p = 0.04), a 6.56-fold (p = 0.03) decrease in TMA levels, a 2.4-fold increase in relative abundance of Ruminococcus and Lachnospiraceae AC 2044 group by 7.5 times and a 2.8-fold decrease in relative representation of Helicobacter. The mechanism of antioxidant effect of orally administered CoQ10 can include modification of the taxonomic composition of the gut microbiota and increased generation of molecular hydrogen, which is antioxidant by itself. The evoked increase in the level of butyric acid can be followed by protection of the gut barrier function.